1989
DOI: 10.1002/bip.360281105
|View full text |Cite
|
Sign up to set email alerts
|

IV characteristics and electrical conductivity of synthetic melanin

Abstract: SynopsisZ -V characteristics for synthetic melanin were investigated a t -10 and 25°C. I t was found that the Ohm law is valid for low voltages whereas the Child law holds for higher ones. Furthermore, the steady state electrical conductivity was estimated. The change of activation energy from 0.76 eV for low temperatures to 1.58 eV was noticeable near 0°C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 9 publications
2
21
1
Order By: Relevance
“…The film was found to have a conductivity of 1.4!10 K6 S/cm under ambient conditions, which is higher than the reported value in the literature of 6.4!10 K8 S/cm [16] for melanin pellets at room temperature under ambient conditions. The increased conductivity is thought to be caused by increased ordering in the polymer grains.…”
Section: Resultscontrasting
confidence: 65%
“…The film was found to have a conductivity of 1.4!10 K6 S/cm under ambient conditions, which is higher than the reported value in the literature of 6.4!10 K8 S/cm [16] for melanin pellets at room temperature under ambient conditions. The increased conductivity is thought to be caused by increased ordering in the polymer grains.…”
Section: Resultscontrasting
confidence: 65%
“…From the data, it was hypothesized that melanin has the ability to act as an amorphous organic semiconductor. The semiconducting properties of melanin have since been demonstrated in several other studies (9,10). In addition, photoconductivity measurements have shown that a current is produced in a eumelanin film under illumination by white light (11,12).…”
Section: Introductionmentioning
confidence: 76%
“…A recent study reveals that the melanin is a hybrid electronic‐ionic conductor in which charge transportation is due to the free radicals (electrons) and hydronium ions (protons) . Furthermore, electrical properties ( I – V ) of the melanin strongly depend on the charges injected from the active electrode and charges generated in the sample . In addition to this, positive (H + ) and negative (OH − ) charged ions may be generated due to dissociation of residual inner water .…”
Section: Resultsmentioning
confidence: 99%
“…Wünsche et al have showed that the electrical response of hydrated eumelanin films is dominated by ionic conduction and electrochemical processes. On the other hand, some results also suggested that the electrical properties of the melanin is strongly depends on the charges injected from the active electrode and charges generated in the sample …”
Section: Introductionmentioning
confidence: 99%